2019
DOI: 10.1021/acs.estlett.9b00022
|View full text |Cite
|
Sign up to set email alerts
|

Observations of High Levels of Ozone-Depleting CFC-11 at a Remote Mountain-Top Site in Southern China

Abstract: A field campaign was carried out in the autumn of 2017 to measure the CFC-11 concentrations at a remote mountain-top site in southern China. During the sampling period, the mixing ratios of CFC-11 (329 ± 9 pptv) were considerably higher than both the regional backgrounds of East Asia (235 ± 1 pptv) and the Northern Hemisphere backgrounds (230 ± 1 pptv). Significantly high levels of CFC-11 were observed in late October, and the high CFC-11 concentrations correlate well with the concentrations of anthropogenic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Rigby et al (2019) discovered an increase of CFC‐11 emissions primarily around the northeastern provinces of Shandong and Hebei in China. Lin et al (2019) reported findings from a field campaign carried out in 2017 that the CFC‐11 concentration in southwestern and central China then was higher than the background measurements in East Asia and the northern hemisphere. All these discoveries were based on surface in situ observations, which cannot provide the global, or at least near‐global, spatial patterns of the trends.…”
Section: Introductionmentioning
confidence: 99%
“…Rigby et al (2019) discovered an increase of CFC‐11 emissions primarily around the northeastern provinces of Shandong and Hebei in China. Lin et al (2019) reported findings from a field campaign carried out in 2017 that the CFC‐11 concentration in southwestern and central China then was higher than the background measurements in East Asia and the northern hemisphere. All these discoveries were based on surface in situ observations, which cannot provide the global, or at least near‐global, spatial patterns of the trends.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent measurements and modelling studies pointed to a significant increase in CFC-11 emissions in East Asia and especially in Eastern China, including Shandong and Hebei provinces [4,14,15]. Later on, a high level of CFC-11, about 30 pptv above the global background values, was observed in China [16,17], which further indicated its unexpected emissions in some regions.…”
Section: Introductionmentioning
confidence: 99%
“…Here, n ij is the total number of endpoints that fall in the ijth cell (Figure S2) and m ij is the number of endpoints for which measured values exceed a specified criterion value in the ijth cell. Previous studies used the mean (Hui et al, 2019;Lin et al, 2019), 50th percentile (Li, Ye, et al, 2016;Polissar et al, 1999), 75th percentile (N. Gao et al, 2012;M. Yang et al, 2021;Zhao et al, 2015), and 90th percentile Fang et al, 2018) as criterion values.…”
Section: Trajectories Clustering and Potential Source Contribution Functionmentioning
confidence: 99%
“…The results of this work expand upon earlier studies locating the origin of CFC-11 emissions. Also applying the PSCF technique, Lin et al (2019) documented that high levels of CFC-11 observed in Nanjing, China in October 2017 originated from less developed regions in southwestern and central China, with a minor fraction emerging from the PRD metropolitan region. M. Yang et al (2021) also used the PSCF method to find high CFC-11 mixing ratios observed from June 2017-April 2018 at Mount Tai (located in Shandong Province) had traveled from Shanxi, Hebei, Anhui, and Henan provinces.…”
Section: Potential Emission Source Regionsmentioning
confidence: 99%